2022
DOI: 10.1093/ofid/ofac183
|View full text |Cite
|
Sign up to set email alerts
|

Rethinking the “Pan-Culture”: Clinical Impact of Respiratory Culturing in Patients With Low Pretest Probability of Ventilator-Associated Pneumonia

Abstract: Background Respiratory cultures are often obtained as part of a “pan-culture” in mechanically ventilated patients in response to new fevers or leukocytosis, despite an absence of clinical or radiographic evidence suggestive of pneumonia. Methods This was a propensity score-stratified cohort study of hospitalized mechanically-ventilated adult patients between 2014-2019, with new abnormal temperature or serum white blood cell c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…The widespread application of ‘pan-culture’ for fever has come into question as it is associated with increased antibiotic use without added clinical benefit and with significant harms, 18 including increased antibiotic use, costs, patient discomfort, and iatrogenic infections. 13 19 On the other hand, since the diagnostic accuracy of clinical exam alone is lacking (60% sensitive and 64% specific), we recommended that the clinical evaluation be supplemented with additional tests selectively guided by the clinical suspicion, patient symptomatology, and/or risk for certain infections.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The widespread application of ‘pan-culture’ for fever has come into question as it is associated with increased antibiotic use without added clinical benefit and with significant harms, 18 including increased antibiotic use, costs, patient discomfort, and iatrogenic infections. 13 19 On the other hand, since the diagnostic accuracy of clinical exam alone is lacking (60% sensitive and 64% specific), we recommended that the clinical evaluation be supplemented with additional tests selectively guided by the clinical suspicion, patient symptomatology, and/or risk for certain infections.…”
Section: Discussionmentioning
confidence: 99%
“… 45 46 Respiratory cultures may help support the diagnosis, but the presence of bacteria on culture is not diagnostic of a pneumonia because a majority of intubated patients will have colonization of the endotracheal tube—this is especially true if tracheal aspirates are used, although the use of bronchioalveolar lavage (BAL) does not eliminate false positives or false negatives. 18 47 Unfortunately, a positive culture is often routinely managed with antibiotics regardless of the diagnostic impression. 25 48 …”
Section: Discussionmentioning
confidence: 99%
“…The overreliance on respiratory culturing to diagnose VAP can be seen in the recent cohort study by Albin et al, who evaluated patients on mechanical ventilation with new abnormal white blood cell (WBC) count or temperature but without radiographic evidence, ventilatory changes or purulent secretion. 56 Amongst the 534 patients studied, 21.2% had respiratory tract sampling for microbial cultures. This respiratory tract culturing was strongly associated with prolonged unnecessary antimicrobial use (OR 2.32; 95% CI 1.23–4.24), including broad-spectrum antimicrobial use (OR 2.23; 95% CI 1.33–3.73).…”
Section: Reviewmentioning
confidence: 99%
“…Interestingly, HCWs from hospitals with the highest culture rates also viewed CDS less favorably. Single-center studies have identified similar themes of excessive endotracheal aspirate culturing including that clinicians or individual units have developed normalized "default" practices (24), have low thresholds to obtain cultures (29,30), have high vigilance for sepsis (26), and have fear of missing infection (24)(25)(26)31). These patterns align with psychologic factors relevant for clinical de-implementation, including difficulty breaking habits, and asymmetry of outcomes or loss aversion (e.g., clinician concern for missing a diagnosis feels stronger than the perception of harm from the intervention) (32).…”
Section: What This Study Meansmentioning
confidence: 99%